Early Mortality after Radical Radiotherapy in Head and Neck Cancer – A Nationwide Analysis from the Danish Head and Neck Cancer Group (DAHANCA) Database. Issue 1 (January 2021) - Jensen, K.H.; Vogelius, I.; Kristensen, C.A.; Andersen, E.; Overgaard, J.; Eriksen, J.G.; Primdahl, H.; Johansen, J.; Farhadi, M.; Andersen, M.; Friborg, J.
Abstract: Aims: Curative-intent radiotherapy (RT) or chemoradiation (CRT) of squamous cell carcinoma of the head and neck (HNSCC) produces high survival rates, but is associated with substantial toxicity. However, there are no commonly accepted quality metrics for early mortality in radiation oncology. To assess the applicability of early mortality as a clinical quality indicator, this study investigated the temporal distribution, risk factors and trends of 90- and 180-day overall and non-cancer mortality in a nationwide cohort of HNSCC patients treated with RT/CRT. Materials and methods: Information on all HNSCC patients treated with curative-intent RT/CRT in Denmark between 2000 and 2017 was obtained from the national Danish Head and Neck Cancer Group clinical database. Deaths in patients with residual or recurrent disease after RT/CRT were classified as cancer-related. Possible risk factors were investigated using logistic regression analysis. Results: Data from 11 419 patients were extracted. In total, 90- and 180-day mortality risks were 3.1% and 7.1%, respectively. There was a uniform temporal distribution of 180-day mortality. In multivariable analysis, increasing age, stage, performance status, earlier treatment year and hypopharyngeal cancer were significantly associated with an increased risk ( P < 0.05). Risk factor estimates were comparable for 90- versus 180-day mortality as well as for overall versus non-cancer mortality. Between 2000 and 2017 there was a significant decrease in 180-day mortality, which was driven by a reduction in cancer-related events. Conclusion: The distribution of 180-day overall and non-cancer mortality did not indicate a well-defined early high-risk period. Moreover, risk factor estimates were highly similar across risk periods and groups. Taken together, our findings question the applicability of early mortality as a standard metric for treatment-associated toxicity. Highlights: Early mortality after radical radiotherapy was investigated in a national head–neck cancer cohor.t 90- and 180-day mortality risks were 3.1% and 7.1%, respectively Early mortality decreased between 2000 and 2017. There were no indications of an early high-risk period after treatment initiation. Introducing early mortality as a clinical quality indicator is questionable